The Computational Fluid Dynamic Simulations for Gangrene Disease in Diabetic Foot - Al-allaq, Ali Amer (Al-Khwarizmi Engineering Journal, 2018)
The diabetic foot is considered one of the long term diabetes complications caused by a defect in blood vessel and nerve system. This requires dealing with diabetic foot with professional medical care, so as to prevent its development in advanced stages which could end to gangrene and amputation of the foot. This study has been initiated through follow-up of twelve patients with diabetes and the presence various occlusions in lower limb artery. One patient from them was chosen for investigation, this patient has stenosis in popliteal artery and presence multiple stenosis in superficial femoral artery. This study based on analysis present case of patient and prediction for progress stenosis in superficial femoral artery till arrive semi total occlusion of the artery and interpret the occurrence of gangrene in the lower limb. The geometrical values of the artery and stenosis were acquired measured directly from the patient by using angiography device. The disease of gangrene and artery stenosis in diabetic foot has been investigated by using a simulation program (ANSYS Fluent CFD). The results of study by using four models with (75%, 90%) stenosis from original artery diameter in the healthy patient case are presented and compared with present and healthy case (without stenosis). It has been appeared, with presence of multi stenosis in superficial femoral artery for diabetic foot, and by assuming the blood to be a Newtonian fluid, a significant increase in the blood velocity and wall shear stress in the area of stenosis compared with non stenosis region. The blood flow rate was decreased constrained as the degree of stenosis increased and vice versa. Peak blood velocity is about (0.88) m/sec for healthy artery, it reaches (2) m/sec for a 42.4% stenosis (current case).The maximum velocity values were (10.36, 49.31) m/sec for 75%, 90% stenosis respectively. The maximum wall shear stress at the stenosis region varies from (1094) pa in the 75% stenosis to (15916) pa in the 90% stenosis against a values of (6.36, 380.5) pa in the healthy artery, current case respectively.